Frequencies of Gag-restricted T-cell escape "footprints" differ across HIV-1 clades A1 and D chronically infected Ugandans irrespective of host HLA B alleles. Issue 14 (30th March 2015) - Serwanga, Jennifer; Nakiboneka, Ritah; Mugaba, Susan; Magambo, Brian; Ndembi, Nicaise; Gotch, Frances; Kaleebu, Pontiano
Highlights: A and D infected subjects even though they bear the same presenting HLA alleles, and live in the same environment. Escape mutations that are known to confer survival advantage were more frequent in clade A-infected subjects irrespective of host HLA alleles. There was no evidence to link this difference in outcome to the evaluated adaptive T-Cell responses (IFN-γ responses and polyfunctional responses) to those key structurally constrained Gag epitopes. However, we have demonstrated that there was significantly greater selective pressure on the Gag protein of clade A than that of clade D. The data are in line with the known faster disease progression in clade D than clade A infected individuals. The data also highlight that the current difficulties in formulating a global HIV vaccine design will be further challenged by clade associated differences in outcome. Abstract: Objective(s): We evaluated relationships between critical Gag T-cell escape mutations and concomitant T-cell responses to determine whether HLA-restricted Gag mutations that confer protection, occur at similar rates in a population infected with mixed HIV-1 clades A1 and D viruses. Methods: Assessment of Gag selective pressure, and adaptive T-cell functions to KAFSPEVIPMF (KF11), ISPRTLNAW (ISW9) and TSTLQEQIGW (TW10) Gag epitopes were combined with host HLA to assess correlations with rates of critical epitope escape mutations in clades A1- ( n  = 23) and D- ( n  = 21) infected, untreated subjects. Infecting clades and selection pressure were determined from the gag sequences. Results: Overall, Gag escape mutations A163X in KF11 were detected in 61% (14/23) A1- infected compared to 5% (1/21) in D-infected subjects ( p  = 0.00015). Gag mutations I147X in the ISW9 epitope were seen in 43%: (10/23) clade A compared to 5%: (1/21) clade D infected subjects, p  = 0.007, Fisher's Exact test. Both mutations were more frequent in clade A1 infection. Frequencies of the measured epitope-specific T-cell responses were comparable across clades. Peptide binding affinities for the restricting HLA alleles did not differ across clades. Overall, selection pressure on the Gag protein was significantly greater in clade A than in clade D sequences. Conclusions: These findings imply that HIV-1 vaccine strategies designed to target structurally constrained T-cell epitopes may be further challenged by clade-driven outcomes in specific HLA-restricted Gag epitopes. Equally, the data are line with slower HIV-1 disease progression in clade A infection; and raise hope that increased selective pressure on Gag may be protective irrespective of host HLA alleles.